2012
DOI: 10.1016/j.neuroscience.2012.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and MK-801 administration leads to alternative N-methyl-d-aspartate receptor 1 splicing and associated changes in reward seeking behavior and nociception on an operant orofacial assay

Abstract: The NMDA receptor plays a large role in opioid-induced plastic changes in the nervous system. The expression levels of its NR1 subunit are altered dramatically by morphine but no changes in its alternative splicing have been reported. Changes in the splicing of the N1, C1, C2, and C2’ cassettes can alter the pharmacology and regulation of this receptor. Western blots run on brain tissue from rats made tolerant to morphine revealed altered splicing of the N1 cassettes in the accumbens and amygdala, and the C1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…No interaction was observed (RM Two-Way, F(5,217)=1.263, p>0.05). Previous studies in our lab demonstrated that morphine was anti-nociceptive at doses of at least 10 mg/kg when tested at the aversive 46°C as well (Anderson et al, 2012). …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…No interaction was observed (RM Two-Way, F(5,217)=1.263, p>0.05). Previous studies in our lab demonstrated that morphine was anti-nociceptive at doses of at least 10 mg/kg when tested at the aversive 46°C as well (Anderson et al, 2012). …”
Section: Resultsmentioning
confidence: 86%
“…We measured the effects of morphine administration and withdrawal on motivational reward-seeking behavior and nociception with a reward/conflict operant task first described by Neubert et al (2005) which is sensitive to morphine (Neubert et al, 2006) and can measure motivation for reward (Anderson et al, 2012). A total of forty rats were fasted for 17 +/− 1hrs (from 5pm the previous night to 9–11am the next day) then placed in a Plexiglas box for ten minute periods and trained to press their faces between two aluminum tubes in order to receive a reward of diluted sweetened condensed milk (2:1 water:milk ratio).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…No differences were observed for the morphine only group, demonstrating this is a morphine withdrawal only effect. These changes in pNR1/ NR1 during acute withdrawal are not caused by changes in NR1 total protein (Anderson et al, 2012b). These changes are also subregion specific, because we tested samples from the amygdala, hippocampus, and periaqueductal gray and found no changes in pNR1 levels (data not shown).…”
Section: Acute Morphine Withdrawal Increases Nr1 Phosphorylation In Tmentioning
confidence: 81%